Culture of animal cells : a manual of basic technique and specialized applications - Freshney, R. Ian (Hoboken, New Jersey : Wiley-Blackwell, 2010)
* This is the sixth edition of the leading text in the basic methodology of cell culture, worldwide. * Updates on molecular hybridization, somatic cell fusion, hybridomas, and DNA transfer
1. Introduction -- 2. Biology of cultured cells -- 3. Laboratory design, layout, and equipment -- 4. Equipment and materials -- 5. Aseptic technique -- 6. Safety, bioethics, and validation -- 7. Culture vessels and substrates -- 8. Defined media and supplements -- 9. Serum-free media -- 10. Preparation and sterilization -- 11. Primary culture -- 12. Subculture and cell lines -- 13. Cloning and selection -- 14. Cell separation -- 15. Characterization -- 16. Differentiation -- 17. Transformation and immortalization -- 18. Contamination -- 19. Cryopreservation -- 20. Quantitation -- 21. Cytotoxicity -- 22. Specialized cells -- 23. Stem cells, germ cells, and amniocytes -- 24. Culture of tumor cells -- 25. Three-dimensional culture -- 26. Scale-up and automation -- 27. Specialized techniques -- 28. Training programs -- 29. Problem solving -- 30. In conclusion
Includes bibliographical references and index
Keywords: Cell culture -- Laboratory manuals; Tissue culture -- Laboratory manuals